Calidad del cuidado de enfermería y satisfacción del adulto post operado inmediato servicio de cirugía Hopital Apoyo Chepén - Bazanelly Condor, Dady Arac (2016)
The present correlational descriptive of cross-cutting research work was carried out in order to determine the relationship between the perception of quality of nursing care and the degree of satisfaction of the immediate post mature adult user of the service of surgery of the Hospital's support network health Chepén. The sample population consisted of 32 patients operated post that met the inclusion criteria. Data collection was carried out through the following instruments: scale on the quality of nursing care according to perception of the user, and scale on the degree of satisfaction according to the user's perception in the surgery of the Hospital's support service network health Chepén. The data were processed using specialized software, applying the statistical test Chi square independence of criteria and reached the following conclusions. 1. 65.62% of mature adult users of the service post-operative surgery Support Hospital Health Network Chepén. They refer to have received poor quality of nursing care, the 34.37% good quality of care, 2. 69% of users refer to be satisfied with the care received, and 31% dissatisfied. 3 there is a significant relationship between the quality of nursing care and the degree of satisfaction of the patient p < 0.05